Development and Validation of the Readiness for End-of-Life Conversations (REOLC) Scale - Berlin, Pia; Leppin, Nico; Nagelschmidt, Katharina; Seifart, Carola; Rief, Winfried; von Blanckenburg, Pia (Frontiers in Psychology, 2021)
Background: Engaging in end-of-life care considerations is beneficial when the time is right. The purpose of this study is to provide a valid instrument to assess peoples’ readi-ness for end-of-life conversations before they are initiated. Materials and Methods: A community sample was recruited in study one for exploratory factor analy-sis of a thirteen-item questionnaire. In study two, psychometric properties were analyzed with structural equation modeling in a population affected by cancer. Convergent and discriminant validity were assessed with questionnaires measuring distress, depression, anxiety, fear of progression and distress of death and dying. Results: In study one (N = 349) exploratory factor analysis resulted in three subscales readiness (α = .84), communication (α = .76) and values (α = .56) with a possible common factor (α = .84) for healthy participants. In study two (N = 84) the three-factor solution with 13 items was not supported for cancer patients. Factor structure was adapted to 12 items with one common factor readiness (α = .87). Model fit was good: χ2(50) = 59.18, p > .05 (Satorra-Bentler-correction=1.27), with χ2/df = 1.184, rRMSEA = .053 (90%-CI[.000; .100]) and rSRMR = .072. Convergent validity was supported by moderate correlations to trait gratitude, ratings of readiness to provide a living will or talk with family about the end of life. Divergent validity was supported by no or small correlation with distress, depression, general and death anxiety and fear of progression, respectively. Conclusions: Results support usage of the REOLC Scale in different settings with adapted factor structure. The questionnaire is interpreted as valid and reliable instrument to assess objective readiness for end-of-life conversations.